2002
DOI: 10.1110/ps.4680102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ejl, the cell‐wall amidase coded by the pneumococcal bacteriophage Ej‐1

Abstract: The Ejl amidase is coded by Ej-1, a temperate phage isolated from the atypical pneumococcus strain 101/87. Like all the pneumococcal cell-wall lysins, Ejl has a bimodular organization; the catalytic region is located in the N-terminal module, and the C-terminal module attaches the enzyme to the choline residues of the pneumococcal cell wall. The structural features of the Ejl amidase, its interaction with choline, and the structural changes accompanying the ligand binding have been characterized by CD and IR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In contrast, the far UV CD spectrum of the Cpl-1 lysozyme ( Fig. 2A) resembles those reported for other properly folded choline-binding proteins (15,17,24), and the CD changes promoted by choline binding take place within the dead time of mixing in both regions of the spectrum. In the near UV region, the interaction with choline primarily sharpened preexisting bands between 279 and 296 nm, increasing their intensities by about 4-fold.…”
Section: Differences In the Native Structures Of Lytc And Cpl-1 Lysozsupporting
confidence: 66%
See 1 more Smart Citation
“…In contrast, the far UV CD spectrum of the Cpl-1 lysozyme ( Fig. 2A) resembles those reported for other properly folded choline-binding proteins (15,17,24), and the CD changes promoted by choline binding take place within the dead time of mixing in both regions of the spectrum. In the near UV region, the interaction with choline primarily sharpened preexisting bands between 279 and 296 nm, increasing their intensities by about 4-fold.…”
Section: Differences In the Native Structures Of Lytc And Cpl-1 Lysozsupporting
confidence: 66%
“…The far UV region of the CD spectrum of murein hydrolases encoded by pneumococcus and its phages is characterized by the presence of a maximum in the region of 224 -230 nm (15,17,24,25), which is sensitive to the interaction of choline with the tryptophan residues present at the binding site (8 -10). Interestingly, the presence of this band in the spectrum of LytC strictly depends on choline binding ( Fig.…”
Section: Differences In the Native Structures Of Lytc And Cpl-1 Lysozmentioning
confidence: 99%
“…Well-studied examples of ligand recognition are the pneumococcal endolysins derived from phages Cp-1 (Cpl-1 endolysin), Dp-1 (PAL endolysin), and Ej-1 (Ej-1 endolysin). Their corresponding CBDs specifically bind choline, which is present only in teichoic acids of the pneumococcal cell wall and which is essential for bacterial viability (52,72,78). Also, the CBDs of the Listeria monocytogenes bacteriophage endolysins Ply118 and Ply500 can bind to different Listeria serovar groups, as visualized by fusions with green fluorescent protein (GFP), showing that they are correlated with the occurrence of somatic antigens related to these serovars (67).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that choline-modified TA in S. pneumoniae increases susceptibility to certain phages (110). Several pneumococcal phages contain proteins homologous to the cholin-binding proteins of S. pneumoniae, and choline-binding interactions have been demonstrated for some of these (111,112). As LPS molecules can serve as phage receptors (113,114), it is possible that ChoP attachment to the LPS affects phage susceptibility in other bacteria as well.…”
Section: Host Responses To Chopmentioning
confidence: 99%